2001
DOI: 10.1080/07315724.2001.10719053
|View full text |Cite
|
Sign up to set email alerts
|

A Hydroxychalcone Derived from Cinnamon Functions as a Mimetic for Insulin in 3T3-L1 Adipocytes

Abstract: Together, these results demonstrate that the MHCP is an effective mimetic of insulin. MHCP may be useful in the treatment of insulin resistance and in the study of the pathways leading to glucose utilization in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
207
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 25 publications
6
207
1
10
Order By: Relevance
“…Previous studies have shown that 1-6 g/day cinnamon powder intake reduces blood glucose, total cholesterol and LDL-Cholesterol in human [16]. Also it is shown that methyl hydroxychalecon, a cinnamon derived component, mimics insulin effects on 3T3-L1 cell line and increases glycogen synthase kinase, glucose uptake and insulin receptor (IR) contents [1]. Other studies have shown GLUT4 enhancement under different concentrations of cinnamon extract or dihydrocinnamic acid (DHH105), a derivative of cinnamon, on GLUT4 content in animal adipose tissue [17] or 3T3-L1 cell line, a good model for studding fat tissue metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that 1-6 g/day cinnamon powder intake reduces blood glucose, total cholesterol and LDL-Cholesterol in human [16]. Also it is shown that methyl hydroxychalecon, a cinnamon derived component, mimics insulin effects on 3T3-L1 cell line and increases glycogen synthase kinase, glucose uptake and insulin receptor (IR) contents [1]. Other studies have shown GLUT4 enhancement under different concentrations of cinnamon extract or dihydrocinnamic acid (DHH105), a derivative of cinnamon, on GLUT4 content in animal adipose tissue [17] or 3T3-L1 cell line, a good model for studding fat tissue metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is the most prevalent metabolic disease worldwide and the most cases are insulin resistant or type-2 diabetic patients [1]. Insulin resistance results to pathologic complications such as hyperinsulinemia, hyperglycemia and glucose toxicity, glucose intolerance, hypertriglyceridemia, high blood pressure, neuropathy, retinopathy, nephropathy, ketoacidosis and death [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro investigations reported the insulinsensitizing effect of cinnamon (1)(2)(3)(4). Using a rat model, Qin et al (5) (2) observed that when cinnamon and insulin were combined in vitro, the effect was greater than was expected, implying a synergistic relationship. Additionally, Kim et al (6) proposed that cinnamon acts by increasing endogenous insulin production, rather than by a target-based mechanism.…”
mentioning
confidence: 99%
“…Anderson et al (1) suggested that doubly linked, water-soluble A-type polymers, possibly misidentified earlier as methylhydroxychalcone polymers (2), are the active compounds. Several in vitro investigations reported the insulinsensitizing effect of cinnamon (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation